PARABOLA GRĂUNTELUI DE MUȘTAR CA FIGURĂ A ISTORIEI MÂNTUIRII. EXERCIȚIU EXEGETIC - VARA, Alin (Studia Universitatis Babeș-Bolyai Theologia Graeco-Catholica Varadiensis, 2024)
The Parable of the Mustard Seed as a Figure of Salvation History. Exegetical exercise. This article takes the parable of the mustard seed as a case study for exposing some exegetical difficulties of New Testament scholarship. The first part evaluates the characteristics, strengths and weaknesses of the major methods of biblical interpretation of the patristic and the modern eras, claiming that one always needs to critically evaluate the underlying philosophical and theological assumptions behind each method. In the second part, I analyze the passage itself in its synoptic morphology, while proposing some views which would help at solving the historical-critical dilemmas of New Testament scholarship.